Local radio and its audience 1980 - Hedman, Lowe (Uppsala University, 1984)
The investigation has been made on the request of the Committee for local radio in 15 places during one week in April 1980. Its purpose was to give information on the standpoint of regular listeners on the role and functions in society of the local radio, their judgement of the single programmes and the total offer of programmes, imaginable effects and their experience of local radio generally.

The investigation has been made on the request of the Committee for local radio in 15 places during one week in April 1980. Its purpose was to give information on the standpoint of regular listeners on the role and functions in society of the local radio, their judgement of the single programmes and the total offer of programmes, imaginable effects and their experience of local radio generally.
Närradion och dess lyssnare 1980
Keywords: Media; Media; Social Sciences; Samhällsvetenskap